2017
DOI: 10.1186/s12931-017-0512-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronic comorbidity and exacerbation risk in primary care patients with COPD

Abstract: BackgroundCOPD often coexists with chronic conditions that may influence disease prognosis. We investigated associations between chronic (co)morbidities and exacerbations in primary care COPD patients.MethodRetrospective cohort study based on 2012–2013 electronic health records from 179 Dutch general practices. Comorbidities from patients with physician-diagnosed COPD were categorized according to International Classification of Primary Care (ICPC) codes. Chi-squared tests, uni- and multivariable logistic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 32 publications
4
91
1
6
Order By: Relevance
“…COPD is associated with many comorbidities 22 , 23 . Anxiety and depression are major contributors to hospital bed usage and readmissions, and should be optimally managed.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD is associated with many comorbidities 22 , 23 . Anxiety and depression are major contributors to hospital bed usage and readmissions, and should be optimally managed.…”
Section: Recommendationsmentioning
confidence: 99%
“…COPD is associated with many comorbidities. 22,23 Anxiety and depression are major contributors to hospital bed usage and readmissions, and should be optimally managed. Mortality from COPD is more associated with cardiac events than respiratory failure, 24 and the importance of avoiding prolonged overuse of b 2 -agonists is becoming increasingly recognised.…”
mentioning
confidence: 99%
“…Additionally, heart failure, visual impairment, lung cancer, depression, prostate disorders, asthma, osteoporosis, diabetes, gastroesophageal reflux, and peripheral vascular disease are significantly associated with frequent (≥2 per year) exacerbations [32,81]. Coexisting asthma has also been shown to significantly increase the frequency of severe exacerbations [82].…”
Section: Association With Other Comorbiditiesmentioning
confidence: 99%
“…Co‐morbidities play a major role in the risk of an ED presentation in patients with COPD, and we do not know the rate of concurrent diagnoses of other diseases that often complicate AECOPD, including pneumonia, heart failure, myocardial ischaemia and diabetes in this study. It is crucial to address these also during an admission, as it has been observed that over half of the readmissions in patients hospitalized for COPD may not be COPD‐related .…”
mentioning
confidence: 90%